2014
DOI: 10.1038/cddis.2014.415
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR pathway inhibitors enhance radiosensitivity in radioresistant prostate cancer cells through inducing apoptosis, reducing autophagy, suppressing NHEJ and HR repair pathways

Abstract: The PI3K/Akt/mTOR pathway has a central role in cancer metastasis and radiotherapy. To develop effective therapeutics to improve radiosensitivity, understanding the possible pathways of radioresistance involved and the effects of a combination of the PI3K/Akt/mTOR inhibitors with radiotherapy on prostate cancer (CaP) radioresistant cells is needed. We found that compared with parent CaP cells, CaP-radioresistant cells demonstrated G0/G1 and S phase arrest, activation of cell cycle check point, autophagy and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
188
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 30 publications
16
188
0
2
Order By: Relevance
“…The PI3K/Akt/mTOR signaling pathway promotes cellular growth, migration, protein synthesis, survival and metabolism in response to growth factors and nutrient availability (8). PI3K activates Akt, which leads to the phosphorylation of mTOR via a number of regulators (17). In the present study, Licochalcone A suppressed the PI3K/Akt/mTOR signaling pathway in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The PI3K/Akt/mTOR signaling pathway promotes cellular growth, migration, protein synthesis, survival and metabolism in response to growth factors and nutrient availability (8). PI3K activates Akt, which leads to the phosphorylation of mTOR via a number of regulators (17). In the present study, Licochalcone A suppressed the PI3K/Akt/mTOR signaling pathway in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 48%
“…Autophagy promotes the survival of cells and maintains homeostasis by degrading damaged organelles and proteins (17). The PI3K/Akt/mTOR signaling pathway promotes cellular growth, migration, protein synthesis, survival and metabolism in response to growth factors and nutrient availability (8).…”
Section: Discussionmentioning
confidence: 99%
“…We found that knockdown of HMBOX1 decreased the expression of ATM, ATR and BRCA1 with or without ionizing radiation exposure, as well as phospho-ATM and phospho-ATR. Previous studies have verified that ATM, and ATR expression levels are closely related to radiosensitivity in cancer cells (20)(21)(22)(23)(24), and inhibition of radiation-induced DNA damage repair is believed to lead to radiosensitization (25). Our data indicate that knockdown of HMBOX1 resulted in lower expression of ATM, ATR and BRCA1 in the HR pathway.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, there are many molecules involved in the control and regulation of sensitivity to irradiation therapy in PCa, and elucidation of the molecular mechanisms underlying the enhanced radioresponse of SQAP is critical. [22][23][24][25][26] SQAP has several characteristics. First, although the agent alone has no substantial effect on tumor growth at low concentrations, it induces radiosensitizing effects.…”
Section: Discussionmentioning
confidence: 99%